(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objectives: The aim of this study was to explore the safety and efficacy of medical management of ectopic pregnancy. Materials and methods: This prospective observational study was conducted between February 2011 to August 2013 in Chittagong Medical College Hospital (CMCH) and in different private clinics of Chittagong city. Twenty-seven patients of ectopic pregnancy conceived by fertility treatment were recruited for medical treatment after proper evaluation. Ectopic pregnancy was diagnosed by serum ?-hCG and progesterone level but missing intrauterine pregnancy by transabdominal sonography (TAS). Serum ?-hCG was repeated after 48 hours to observe doubling of the level. If level was not doubled or increment was not at least 66% and serum progesterone level was less than 15ng/ml then it was considered as ectopic pregnancy. Patients were treated with Injection methotrexate 50 mg intramuscularly either by single dose or two doses. After 4 days of 1st injection ?-hCG was repeated and if level decreased > 15% then patients were assessed weekly till ?-hCG fell to <5lU/L. If drop was <15% after 4 days a second dose of methotrexate was given. Results: Overall success rate was 66.66% . Surgical intervention was needed in 22.22% patients. All patients were treated after hospitalization in CMCH and different private clinics of Chittagong. They got injection methotrexate, antibiotic, antispasmodic and analgesics for abdominal pain. Single dose cured 55.55% patients and 11.11% patients needed second dose, another 11.11% patients were misdiagnosed later on they were diagnosed as intrauterine pregnancy and medical termination was done. Within one year of treatment 33.33% patients conceived again. There was no side effect or complications of the treatment. Conclusion: This small trial gave a good impression about medical treatment in selective cases. The efficacy should be assessed in a randomized clinical trial with a different set of population Bangladesh J Obstet Gynaecol, 2014; Vol. 29(1) : 32-36